A STUDY ON THE EMPOWERING TEACHERS’ PROFESSIONAL DEVELOPMENT AND QUALITY ASSURANCE TO INCREASE TEACHERS’ EFFECTIVENESS IN VOCATIONAL SECONDARY SCHOOLS - Istanto Wahyu Djatmiko (Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
This study is to remind teachers that professional development and quality assurance are required to perform a good working in improving either learning process or school quality. Nowadays, teaching has been officially recognized as a profession. Consequently, teachers must be enforced professionally in their charges. To be professional in carrying their tasks, teachers must continuously improve competency themselves and perform quality assurance in their duties. This study is a literature review related to the importance of professional development and quality assurance in order to increase teachers’ effectiveness in providing learning services in Secondary Vocational Schools. Professional development is the need required by any teachers. Teachers’ professional development in Vocational Secondary School is expected to create changes in attitudes, improve the learning process and promote the students’ learning output and outcomes. In addition, teachers are not only responsible for improving the quality of learning outputs but also for working collaboratively with other teachers to elevate the quality of learning outcomes. It suggests the quality assurance as the key to achieve and to ensure the quality of teaching learning process and also the school’s effectiveness demanded by the stakeholders.